Review V. ILGUNAS, E. JARONIS, V. SITICACICAS, Ultrasonic interferometry (in Russian), Vilna 1983 - Ignacy MALECKI (Archives of Acoustics)
The monograph gives the theoretical fundamentals and the results of experimental research carried out in the ultrasonic laboratory of the Polytechnical Institute in Kaunas, headed by Prof. BARSAUSKAS. In addition to a complex representation of the problems of ultrasonic interferometry, the book contains a number of original achievements of its authors, which deserve above all attention.